IMPACT OF NOISE POLLUTION ON THE ACADEMIC PERFORMANCE OF STUDENTS IN THE UNIVERSITY OF ILORIN’S LEARNING ENVIRONMENT, NIGERIA - Agaja, Toluwalope Mubo; Akande, Gbotemi Peter (FUDMA Journal of Earth and Environmental Sciences, 2024)
Chronic noise exposure in communities near air, road, and/or rail traffic, as a stressor and distraction, can lead to adverse health outcomes and reduced academic performance among adults and children at schools and homes. This study examined the effect of noise pollution on students' academic performance within the University of Ilorin's learning environment, highlighting the environmental impacts of elevated noise levels. Specifically, the study objectives include identifying the sources and intensity of noise within the university environment, its effect on student performance relative to WHO standards, and its impact on student health. Data were collected through a survey administered to 396 students, including undergraduates, postgraduates, and sandwich students. Noise levels were measured using a noise meter across various university locations. Descriptive and inferential statistics, as well as spatial analysis techniques, were applied to the collected data. The results showed that noise levels across the university environment ranged from 77.4 to 95.1 dB, significantly exceeding the WHO recommended threshold of 35dB for schools. Spatial variations in noise pollution were observed, with higher levels in the faculties of Arts, Education, Sciences, Physical Sciences, and Veterinary Sciences. The dominant sources of noise pollution were student social activities, including campaigns and elections, along with generator and vehicular noise. The environmental impact of these elevated noise levels is profound, doubling WHO's minimum noise standards for educational settings. This study concludes that the high noise levels within the university environment are detrimental to both the academic and environmental quality of the ecosystem. It highlights the need for better land use planning and infrastructure development to create sufficient buffers between noise-generating activities and academic spaces, thereby mitigating both environmental and educational impacts.